Elements of multimedia on the Internet - Zeki, Akram M.; Badi, Maimona J. (IIUM Press, 2015)
With the fast improvement in Internet speed and high technology in various devices, applying multimedia elements became so easy and important in daily life use. Different area in business and general uses are applying multimedia elements to improve the human interaction with devices through Internet. This also improves the worldwide communications anywhere anytime. The faster Internet connection and powerful processing capability has improved the multimedia content delivery.